2019
DOI: 10.1039/c9nr04344f
|View full text |Cite
|
Sign up to set email alerts
|

A precursor-approach in constructing 3D ITO electrodes for the improved performance of photosystem I-cyt c photobioelectrodes

Abstract: A precursor-based approach has been employed for the construction of scalable, transparent 3D photobioelectrodes based on PSI and cyt c. An improved transparancy and high photocurrents can be achieved as compared to nanoparticle-based preparation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 364 publications
(546 reference statements)
0
39
1
3
Order By: Relevance
“…The macro‐ITO cathodes achieve a peak cathodic photocurrent of 42.4±5.2 μA cm −2 , the meso‐ITO yield 10.7±0.9 μA cm −2 , and the planar ITO gives 1.1±0.6 μA cm −2 at a PSI loading of 132 mol cm −2 . We also tested porous PSI‐ITO cathodes with pore sizes of 500 nm because similar pore sizes have been shown to be optimal for photocurrent generation by PSI and cyt c . However, the 500 nm pore cathodes produced photocurrent values comparable to the meso‐ITO (Figure S9).…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…The macro‐ITO cathodes achieve a peak cathodic photocurrent of 42.4±5.2 μA cm −2 , the meso‐ITO yield 10.7±0.9 μA cm −2 , and the planar ITO gives 1.1±0.6 μA cm −2 at a PSI loading of 132 mol cm −2 . We also tested porous PSI‐ITO cathodes with pore sizes of 500 nm because similar pore sizes have been shown to be optimal for photocurrent generation by PSI and cyt c . However, the 500 nm pore cathodes produced photocurrent values comparable to the meso‐ITO (Figure S9).…”
Section: Resultsmentioning
confidence: 76%
“…found that porous ITO electrodes incorporating cyt c as a linking agent show a maximum performance of 270 μA cm −2 at the 460 nm pore size in comparison to macropores up to 3 μm with an applied potential of 200 mV vs. Ag/AgCl. The maximum is attributed to a maximum areal loading of cyt c and PSI on the ITO surface due to a higher protein binding capacity within smaller pores . These reports have shown that porous ITO is an effective cathode material for PSI‐based bioelectrodes in conjunction with cyt c and an applied potential to drive DET.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations